Women and the Transmission of the Quran: Marginalization, Legal Strategies, and Maqāṣid al-Sharī‘ah-Based Resolution - Wibowo, Safrudin Edi; Fathiyaturrahmah, Fathiyaturrahmah (AHKAM : Jurnal Ilmu Syariah, 2025)
The duty to maintain the authenticity of the Quran through verbal transmission is a collective obligation for every Muslim. However, several groups of Muslim scholars marginalize the role of women in the transmission of the Quran due to some fiqh rules. Various ethical-legal-formal rules governing women's association in the public space have limited women's access to the transmission process. This study explains the biographical evidence of women's marginalization, the causal factors restricting women's access to the transmission, and the implications and legal strategies women used to overcome these fiqh rules constraints. This is library research with a feminist approach and descriptive analysis. Data collection was carried out by observing literature through library research related to the role of women in the transmission of the Quran. This study showed women's marginalization due to an understanding of gender-biased Islamic doctrines regarding seclusion, prohibitions on traveling and mixing with men (ikhtilāṭ), and the doctrine of women's voices as awrah. Under these conditions, women develop some legal stratagems to break through these religious doctrines. This study recommends using the maqashid al-sharī'ah approach in resolving the problem of marginalization of women in the transmission of the Qur'an.Abstrak:Kewajiban menjaga otentisitas Al-Qur’an melalui transmisi verbal merupakan kewajiban kolektif bagi setiap Muslim, baik laki-laki maupun perempuan. Namun, peran perempuan dalam transmisi Al-Qur'an masih terpinggirkan karena adanya sejumlah pembatasan aturan fiqih yang yang membatasi akses perempuan dalam proses transmisi. Studi ini bertujuan untuk mengeksplorasi bentuk-bentuk marginalisasi perempuan dalam transmisi Al-Qur’an, faktor-faktor penyebab, serta strategi hukum yang digunakan perempuan untuk mengatasi kendala-kendala tersebut. Studi ini merupakan studi pustaka dengan pendekatan feminis. Pengumpulan data dilakukan dengan pengamatan literatur melalui library research terkait peran perempuan dalam transmisi Al-Qur’an. Studi ini menunjukkan bahwa marginalisasi juru baca perempuan mewujud bentuk eksklusi nama-nama juru baca perempuan dari koleksi biografis juru baca Al-Qur’an dan mata rantai sanad Al-Qur’an, serta larangan perempuan untuk membaca Al-Qur’an di ruang publik. Marginalisasi terjadi akibat adanya sejumlah aturan fiqih yang membatasi pergaulan perempuan di ruang publik, seperti perintah pemingitan, larangan bepergian dan bercampur dengan laki-laki asing, serta stigma suara perempuan aurat. Meski demikian, pembatasan-pembatasan tersebut menginspirasi juru baca perempuan untuk mengembangkan strategi hukum guna mengatasi halangan-halangan normatif tersebut. Studi ini merekomendasikan penggunaan pendekatan maqashid al-shari’ah dalam menyelesaikan problem marginalisasi perempuan dalam transmisi Al-Qur’an.